A new endemic species of Vera-duthiea (Hyacinthaceae subfam. Urgineoideae) from Oman - Patzelt, Annette; Pinter, Michael; Martínez-Azorín, Mario (Phytotaxa, 2021)
A new species of Vera-duthiea (Hyacinthaceae) is described from the southern parts of the Dhofar province of Oman. The species is fully described and illustrated, including information on its taxonomic relationships, biology, habitat and distribution. An assessment of its conservation status is also provided.